Structure and Gas Transmission Properties of Surface Modified Food Packaging Materials by Layer-By Assembly - Koca, Nazan; Bayramoğlu, Beste (Izmir Institute of Technology, 2019)
In this study, two different LbL coatings of chicken egg white lysozyme (LZ) (0.2 % w/v)-gum arabic (GA) (0.2 % w/v) and lysozyme (LZ) (0.2 % w/v)-iota carrageenan (IC) (0.2 % w/v) were investigated as a potential agent in the fabricaton of surfacemodified food packaging materials with improved gas barrier properties. The effects of solution pH, adsorption time, number of layers, and inclusion of drying step in between deposition steps on multilayer formation were explored for both LbL coatings seperately. Film growth was monitored up to 10 layers by UV-Vis spectrometry and Surface Plasmon Resonance (SPR), which allows for in situ observation of the multilayer formation. The LbL coatings were characterized by AFM (Atomic Force Microscopy) and SEM (Scanning Electron Microscopy). The oxygen and water vapor transmission rates of the coatings (assembled on corona treated polypropylene (PP) films) were also measured. The most successful LbL assembly was obtained at pH 7-7 combination, with 20 minutes adsorption time and with intermediate drying steps for both (LZ-GA and LZ-IC) LbL coatings. For both LbL coating, both the UV-Vis and SPR measurements showed the similar zig-zag trend; i.e. desorption of some of the pre-adsorbed LZ from the interface with the deposition of GA (or IC) on it, probably due to formation of soluble complexes between them. The importance of intermediate drying steps was established by UV-Vis, AFM and gas transmission rate measurements. The absence of intermediate drying caused a reduction in total mass deposited and the gas barrier properties of the coatings.

Bu çalışmada, lizozim (LZ) (0.2 % w/v) – arap zamkı (GA) (0.2 % w/v) ve lizozim (0.2 % w/v)-iota karragenan (IC) (0.2 % w/v) olmak üzere katmanlı depozisyon (LbL) yöntemi ile hazırlanan iki farklı kaplama, gaz bariyer özellikleri geliştirilmiş, yüzeyi modifiye edilmiş gıda paketleme malzemelerinin üretilmesinde potansiyel bir ajan olarak incelenmiştir. pH, adsorpsiyon süresi, katman sayısı ve kurutma adımının tüm katmanlara dahil edilmesinin film oluşumuna etkileri her iki LbL kaplama için ayrı ayrı incelenmiştir. Film oluşumu 10. katmana kadar, UV-Vis spektrometre ve yüzey plazmon rezonansı (YPR) ile ‘yerinde’ takip edilmiştir. Çok katmanlı filmler atomik kuvvet mikroskobu (AKM) ve taramalı elektron mikroskobu (TEM) ile karakterize edilmiştir. Ayrıca koronalı polipropilen üzerinde oluşturulan LbL kaplamaların oksijen ve su buharı geçirgenliği ölçülmüştür. Her iki film için (LZ-GA, LZ-IC) de, en başarılı LbL kaplama, pH 7-7 kombinasyonunda, 20 dakika adsorpsiyon süresi ile ve kurutma adımının tüm katmanlarda uygulanması halinde elde edilmiştir. Her iki LbL kaplama için, hem UV-Vis hem de YPR sonuçları kaplama oluşumunda aynı eğilimi göstermiştir. Buna göre, önceki adımda adsorbe olan LZ’nin bir kısmının, sonraki GA (veya IC) depozisyon adımında, muhtemelen LZ ve GA (veya IC) arasında çözünebilen komplekslerin oluşması nedeniyle, arayüzeyden geri salındığı anlaşılmıştır. Katmanlar arası kurutma adımının önemi UV-Vis, AKM ve gaz iletim hızı ölçümleri ile belirlenmiştir. Katmanlar arası kurutma adımının olmaması, adsorbe olan toplam kütlede ve kaplamaların gaz bariyer özelliklerinde azalmaya neden olmuştur.
Katmanlı Depozisyon ile Yüzeyi Modifiye Edilmiş Gıda Paketleme Malzemelerinin Yapısal ve Gaz Geçirgenliği Özellikleri
Thesis (Master)--Izmir Institute of Technology, Food Engineering, Izmir, 2019
Full text release delayed at author's request until 2020.11.10
Includes bibliographical references (leaves: 67-74)
Text in English; Abstract: Turkish and English
Keywords: Food packaging; Gas transmission; LbL assembly; Fresh fruits